Study of Biological Behavior and Antimicrobial Properties of Cerium Oxide Nanoparticles - Iason Chatzimentor; Ioannis Tsamesidis; Maria-Eleni Ioannou; Georgia K. Pouroutzidou; Anastasia Beketova; Veronica Giourieva; Rigini Papi; Eleana Kontonasaki (MDPI AG, 2023)
(1) Background: An element that has gained much attention in industrial and biomedical fields is Cerium (Ce). CeO2 nanoparticles have been proven to be promising regarding their different biomedical applications for the control of infection and inflammation. The aim of the present study was to investigate the biological properties and antimicrobial behavior of cerium oxide (CeO2) nanoparticles (NPs). (2) Methods: The investigation of the NPs' biocompatibility with human periodontal ligament cells (hPDLCs) was evaluated via the MTT assay. Measurement of alkaline phosphatase (ALP) levels and alizarine red staining (ARS) were used as markers in the investigation of CeO2 NPs' capacity to induce the osteogenic differentiation of hPDLCs. Induced inflammatory stress conditions were applied to hPDLCs with H2O2 to estimate the influence of CeO2 NPs on the viability of cells under these conditions, as well as to reveal any ROS scavenging properties. Total antioxidant capacity (TAC) of cell lysates with NPs was also investigated. Finally, the macro broth dilution method was the method of choice for checking the antibacterial capacity of CeO2 against the anaerobic pathogens Porphyromonas gingivalis and Prevotella intermedia. (3) Results: Cell viability assay indicated that hPDLCs increase their proliferation rate in a time-dependent manner in the presence of CeO2 NPs. ALP and ARS measurements showed that CeO2 NPs can promote the osteogenic differentiation of hPDLCs. In addition, the MTT assay and ROS determination demonstrated some interesting results concerning the viability of cells under oxidative stress conditions and, respectively, the capability of NPs to decrease free radical levels over the course of time. Antimicrobial toxicity was observed mainly against P. gingivalis. (4) Conclusions: CeO2 NPs could provide an excellent choice for use in clinical practices as they could prohibit bacterial proliferation and control inflammatory conditions.